Perspektif Cendekiawan Buddhis Indonesia tentang Mediokritas Peran Mahasiswa Perguruan Tinggi Keagamaan Buddha sebagai Agent Of Change - Karniawan, Arya Whisnu; Isomudin, Isomudin; Dharmika, Ida Bagus; Sugiyarti, Ririn; Linawati, Linawati (ALACRITY : Journal of Education, 2022)
Development of technology in various fields is increasing rapidly. Younger generation will face competition from two things, namely competition between individuals and competition with robots/AI. Unfortunately, many of Indonesia's young generation adhere to the mindset of "Mediocrity". This mediocrity is loved by various levels of society, including Buddhist Colleges students in Jabodetabek. However, there has been no research that addresses the mediocrity of Buddhist Colleges students in Jabodetabek in their role as agents of change. Various perspectives are needed from existing organizations of Indonesian Buddhist scholars on the role of Buddhist Colleges students in Jabodetabek as agents of change. Is it good, or tend to be mediocre? As well as solutions to the Tipitaka values that can be implemented to overcome this problem. The type of research used is qualitative. The data collection technique used unstructured in-depth interviews and quoted directly from various sources. Data analysis used data interpretation and heuristics. The objectivity and validity of the data used the Mahapadessa parallelization and triangulation methods. The results of this research is based on the analysis of the four dimensions of the agent of change, namely the catalyst; resource linker; solution giver; and process helper, on average Buddhist Colleges students in Jabodetabek tend to be mediocre in carrying out their duties as agents of change. As well as solutions These solutions are scattered in various existing canons. In this case, the researcher tries to summarize the various existing canons as a solution approach to overcome the mediocrity mindset based on the Tipitaka, namely: Generating determination and changing mindsets; Analyze the advantages & disadvantages and determine goals / ideals; Find a good place/environment to grow; Avoid wrong associations and associate with good people; Expanding relationships with four ways of treating others; Continuously learning and self-evaluating; Keep practicing and trying to develop your potential.